Evaluation of the Functional Outcomes of Arthroscopic Surgical Treatment of Complete Rotator Cuff Lesion with Minimum Follow-up of 10 Years - Godinho, André Couto; Santos, Flávio Márcio Lago; Donato Neto, Francisco Pereira; Silva, Paulo Victor Nunes Paz; Fonseca Júnior, Ricardo Dantas (Revista Brasileira de Ortopedia, 2020)
Objectives To analyze the functional outcomes in patients submitted to videoarthroscopic surgical treatment for compleat rotator cuff tears of the shoulder, with a minimum follow-up of 10 years.Methods A total of 63 patients (63 shoulders) underwent videoarthroscopic surgical repair for compleat rotator cuff tears with a minimum follow-up of 10 years. The postoperative functional outcomes of these patients were evaluated using the Constant and University of California at Los Angeles (UCLA) scores.Results The functional evaluation revealed mean UCLA and Constant scores of 26 and 93 points, respectively. Ninety-one percent of the subjects had satisfactory Constant scores, whereas 62% presented satisfactory UCLA scores.Conclusion The arthroscopic repair of rotator cuff complete tear was effective even in the long term (minimum follow-up period of 10 years). The age of the patients before surgery, size of the lesion, the degree of fatty infiltration, and evaluation of muscle trophism are important predictors of prognosis.
Keywords: shoulder; arthroscopy; rupture; rotator cuff; evaluation studies